Effect of intercropping millets, pulses and oilseeds on yield and economics of castor (Ricinus communis) under rainfed conditions - BASITH, M A; MOHAMMAD, SHAIK (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted at NAARM during kharif 2007 and 2008 to find out suitable intercrop to be planted in castor under rainfed conditions. There were six intercrops, viz sorghum, pearl millet, greengram, blackgram, soybean and sunflower tested under two planting geometries of the base crop castor. The results of the experiment showed that the intercropping of two rows of blackgram between the uniform rows of castor produced additional yield of 338 and 266 kg/ha without reducing the yield of castor during the two years respectively. The intercropping of two rows of blackgram or greengram in uniform rows of castor or three rows between the paired rows of castor emerged as statistically superior systems with higher crop equivalent yields than the sole crops during both the years of investigation. The intercropping of greengram and blackgram between uniform rows of castor maximized the gross and net returns per hectare and the RNR indices during the two years. The study confirmed that under divergent conditions of rainfall both in quantity and distribution castor planted in uniform rows at spacing of 90 cm can be efficiently intercropped with two rows of blackgram. This will produce bonus yield of the pulse. The intercropping of greengram was also equally profitable.